Promotion of Calcium/Calmodulin‐Dependent Protein Kinase 4 by GLUT1‐Dependent Glycolysis in Systemic Lupus Erythematosus. Issue 5 (20th March 2019) - Koga, Tomohiro; Sato, Tomohito; Furukawa, Kaori; Morimoto, Shimpei; Endo, Yushiro; Umeda, Masataka; Sumiyoshi, Remi; Fukui, Shoichi; Kawashiri, Shin‐ya; Iwamoto, Naoki; Ichinose, Kunihiro; Tamai, Mami; et al.
Abstract : Objective: To clarify the significance of immunometabolism in systemic lupus erythematosus (SLE), and to determine the effect of calcium/calmodulin‐dependent protein kinase 4 (CaMK4) on T cell metabolism. Methods: Metabolomic profiling was performed using capillary electrophoresis mass spectrometry in naive T cells from MRL/ lpr mice treated with anti‐CD3/CD28 antibodies in the absence or presence of a CaMK4 inhibitor (KN‐93). The expression of GLUT1 and CaMK4 in CD4+ T cells from healthy controls (n = 16), patients with inactive SLE (n = 13), and patients with active SLE (n = 14) was examined by flow cytometry and quantitative polymerase chain reaction. In vitro experiments were performed to determine the effect of KN‐93 on the expression of GLUT1 during Th17 cell differentiation in T cells from patients with SLE. Results: CaMK4 inhibition significantly decreased the levels of glycolytic intermediates such as glucose‐6‐phosphate, fructose‐6‐phosphate, fructose‐1, 6‐diphosphate, pyruvate, and lactate ( P  < 0.05), whereas it did not affect the levels of the pentose phosphate pathway intermediates such as 6‐phospho‐d ‐gluconate, ribulose‐5‐phosphate, ribose‐5‐phosphate, and phosphoribosyl pyrophosphate. The expression levels of GLUT1 and CaMK4 in effector memory CD4+ T cells were significantly higher in patients with active SLE compared to healthy controls ( P  < 0.01 and P  < 0.05, respectively) and patients with inactive SLE ( P  < 0.05 and P  < 0.01, respectively). A functional analysis revealed that CaMK4 inhibition decreased the expression of GLUT1 during Th17 cell differentiation ( P  < 0.01), followed by a reduction of interleukin‐17 (IL‐17) production ( P  < 0.05). Conclusion: The results of the study indicate that the activity of CaMK4 could be responsible for glycolysis, which contributes to the production of IL‐17, and CaMK4 may contribute to aberrant expression of GLUT1 in T cells from patients with active SLE.